Parotid Tumor: A review of seven years’ experience - Shah, Surendra; Shah, Jay Nath; Gongal, Rajesh Nath; Shrestha, Sameer; Poudyal, Sanjay (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Parotid tumors represent about 80% of all salivary gland tumors. Our study was conducted to assess the clinical features, diagnostic accuracy of fine needle aspiration cytology (FNAC), surgical outcome and histological pattern of all patients underwent parotid surgery for parotid tumor at Patan Hospital. Methods: All data of patients who underwent parotid surgery from 2060 to 2067 BC at Patan Hospital were collected retrospectively from medical files and analyzed. Results: Among 18, all were presented with lump in the parotid region. Mean age of the patients was 45 years. Malignancy was common among older age group (mean age 51 vs 44 for benign). The overall accuracy in detecting malignant tumors was 88.89% with positive predictive and negative predictive values 100% and 83.24% respectively. Out of 18 histological reports, 15(83.33%) were benign lesions, pleomorphic adenoma was being most common 9(60%) among benign lesions, and 3(16.67%) were malignant lesions. Conclusion: Painless lump is most common presentation of the parotid tumor. Benign pathology is common and majority of them are pleomorphic adenoma. Malignancy is prevalent in older age group.